War : a primer for Christians - Allen, Joseph L., 1928- (College Station : Texas A & M University Press, 2014)
War: A Primer for Christians provides a concise introduction to the main approaches that Christians have taken toward war and examines each approach critically. Some Christians have supported their country's wars as crusades of good against evil. Others, as pacifists, have rejected participation in or support for any war. Still others have followed the just-war tradition in holding that it can be justifiable under some conditions to resort to war, but that then Christian love must limit the conduct of war. In an updated preface and new afterword, Allen explores aspects of current internationa.
Is war a crusade? -- Some expressions of a crusade approach -- The convictions and logic of the crusade -- Strengths and weaknesses of a crusade approach -- The pacifist standpoint -- Pacifism in the Christian tradition -- The convictions and logic of pacifism -- Strengths and weaknesses of a Christian pacifist -- Just-war thinking -- The Christian just-war tradition -- Underlying convictions of just-war thinking -- Just-war criteria -- Strengths and weaknesses of Christian just-war thinking -- What can we do? -- General observations -- Some responses Christians can make -- Afterword -- The present international situation -- Some implications for moral reflection about war.
The Texas A & M University Press edition includes an updated preface and a new afterword.
Includes bibliographical references.
Print version record.
Master record variable field(s) change: 050
Keywords: War -- Religious aspects -- Christianity; Peace -- Religious aspects -- Christianity; Just war doctrine; Pacifism; Peace -- Religious aspects -- Christianity; Sociology, Christian; War -- Religious aspects -- Christianity; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Just war doctrine; Pacifism; Peace -- Religious aspects -- Christianity; War -- Religious aspects -- Christianity; Electronic books